If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -3 = -3x + 9 + 2x Reorder the terms: -3 + 5x = -3x + 9 + 2x Reorder the terms: -3 + 5x = 9 + -3x + 2x Combine like terms: -3x + 2x = -1x -3 + 5x = 9 + -1x Solving -3 + 5x = 9 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. -3 + 5x + x = 9 + -1x + x Combine like terms: 5x + x = 6x -3 + 6x = 9 + -1x + x Combine like terms: -1x + x = 0 -3 + 6x = 9 + 0 -3 + 6x = 9 Add '3' to each side of the equation. -3 + 3 + 6x = 9 + 3 Combine like terms: -3 + 3 = 0 0 + 6x = 9 + 3 6x = 9 + 3 Combine like terms: 9 + 3 = 12 6x = 12 Divide each side by '6'. x = 2 Simplifying x = 2
| -7-6x=23 | | 2/(x-7)=1/x | | 3y-6=5y+15-21 | | a^2+31=607 | | -5=3x+4+6x | | f^2+64=353 | | w^2+97=113 | | 5+3-2m+3(6+3m)=7m+3(5m-2) | | x+x+5=39 | | -7+5=-11x+17 | | 6x^2+11=49 | | 17x=100 | | -10x+-30=-8x | | 6x+4y+7z-4x+5z-8y= | | 150=2x^3+x^2+x+10 | | H=15t | | B=1.0 | | y-.666666667=5 | | 4(v-9)=-6v+34 | | 2x+7*-1=5 | | -31x-4x=-5-5+25x | | -10x=-8x-8 | | 28x^3+48x^7= | | (x-1)/2/5/4 | | 4n-6+4n=2 | | 9x^4-24x^3-26x^2+56x-15=0 | | 4x^2-11=26 | | f(x)=9x^4-24x^3-26x^2+56x-15 | | 49v-90=-6v+34 | | -5-8=5x+9x-21x | | 192=3X | | -8x^2=-64 |